2020
DOI: 10.5603/gp.2020.0075
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopy Protocols 2020

Abstract: Robert Jach et al., Polish guidelines for colposcopy practice www. journals.viamedica.pl/ginekologia_polska The Consensus was developed by clinical experts of the Comprehensive Colposcopy Standards Recommendations Committee "Colposcopy 2020"The Working Group No. 1 of the Colposcopy Protocols Board Robert Jach -chair Kazimierz Pityński -vice-chair Maciej Mazurec -secretary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The similarities to the HRHPV14-positivity of our results in all categories of abnormal cytological diagnoses were noted. Our HRHPV14-positivity rate of 48.9% for ASC-US cytology cases was within the levels reported for the US conditions, including CAP (47.73%) [31] and the Kaiser Permanente Northern California Foundation (48.39%) [17]. A meta-analysis of Arbyn et al showed an average HRHPV-positivity rate for ASC-US cytology of 43.0%, but it should be remembered that slightly lower levels compared to ours in this case might be associated with the use of a different HRHPV test, which detects less high-risk types [32] than in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The similarities to the HRHPV14-positivity of our results in all categories of abnormal cytological diagnoses were noted. Our HRHPV14-positivity rate of 48.9% for ASC-US cytology cases was within the levels reported for the US conditions, including CAP (47.73%) [31] and the Kaiser Permanente Northern California Foundation (48.39%) [17]. A meta-analysis of Arbyn et al showed an average HRHPV-positivity rate for ASC-US cytology of 43.0%, but it should be remembered that slightly lower levels compared to ours in this case might be associated with the use of a different HRHPV test, which detects less high-risk types [32] than in our study.…”
Section: Discussionsupporting
confidence: 80%
“…The effectiveness of the extended screening strategy in the HPV-based model with p16/Ki67 testing has been confirmed by FDA registration [15]. The limitations of the Polish population-based screening, the preferences of Polish women, and the growing awareness of private sector gynecologists in the new paradigms of secondary cervical cancer prevention result in the gradual implementation of the globally recommended HPV-based screening strategies with proven higher effectiveness [2,16] in Polish private gynecological care [17,18]. Interim screening guidelines in the SARS-CoV-2 pandemic of 2021 [18] include the 2019 risk-based management guidelines of the American Society of Colposcopy and Cervical Pathology (ASCCP) [16] as one of the screening options.…”
Section: Introductionmentioning
confidence: 98%
“…However, we are aware that any change to the current protocols would take time, validation through scientific data, and discussion within accredited societies. We are also convinced that this policy would indeed mean not only a big change in colposcopy practice, first of all in follow-up timing modifications and delayed referral to colposcopy for ASC-US/LSIL cases positive for lowest risk HPV group genotypes (35,39,51,56,59, 66 and 68), but also less costs and less patient anxiety. A stratification of each patient's own risk of CIN3+ at screening could help towards tailored management [14,[22][23][24].…”
Section: Applying Risk-based Stratification To the Italian Screening Settingmentioning
confidence: 94%
“…The addition of HPV 31 to HPV 16/18, as part of a primary HPV screening algorithm recommendation for colposcopy, offers potential benefits for the detection of high-grade cervical disease in the NILM cytology population [20]. Human papillomavirus 16 consistently carried the highest risk for CIN3+ (approximately 15-35% for any cytology and approximately 8-25% for normal cytology), HPV 31, 18, and 33 carried intermediate-high risk for CIN3+ (ranging from approximately 8% to 20% in any cytology and approximately 5% to 10% in normal cytology), HPV 52, 58, and 45 carried moderate risks, with HPV 35,39,51,56,59, 66, and 68 consistently having the lowest CIN3+ rates, regardless of cytology [20][21][22][23]. While recent studies highlight the possible role of HPV genotyping for clinical management of abnormal screening results, further evidence is still needed to assess both, the value of genotyping in different clinical settings (screening, diagnosis, treatment, and follow-up) and the additional risk stratification of more detailed genotyping.…”
Section: Primary Screening Test and Colposcopy In The Vaccination Eramentioning
confidence: 99%
See 1 more Smart Citation